High altitude and free radicals - Bakonyi, T.; Radak, Z. (Journal of Sports Science & Medicine, 2004)
High altitude exposure results in decreased oxygen pressure and an increased formation of reactive oxygen and nitrogen species (RONS), which is often associated with increases in oxidative damage to lipids, proteins and DNA. Exposure to high altitude appears to decrease the activity and effectiveness of antioxidant enzymes system. Moreover, during high altitude exposure several RONS generating source are activated, including mitochondrial electron transport chain, xanthine oxidase, and nitric oxide synthase (NO). Physical exercise at high altitude can further enhance the oxidative stress. The available information suggests that RONS are involved and are even a causative factor of acute mountain sickness. Supplementation of antioxidant seems to be a necessary step to prevent or decrease to high altitude exposure associated oxidative stress.